In vivo characterization of sAC null sperm - Ritagliati, Carla; Ayoub, Sylvia; Balbach, Melanie; Buck, Jochen; Levin, Lonny R. (Frontiers in Cell and Developmental Biology, 2023)
Targeted disruption of the soluble adenylyl cyclase (ADCY10; sAC) gene results in male-specific sterility without affecting spermatogenesis, mating behavior, or spermatozoa morphology and count; however, it dramatically impairs sperm motility and prevents capacitation. These phenotypes were identified in sperm from sAC null mice surgically extracted from the epididymis and studied in vitro. Epididymal sperm are dormant, and never exposed to physiological activators in semen or the female reproductive tract. To study sAC null sperm under conditions which more closely resemble natural fertilization, we explored phenotypes of ejaculated sAC null sperm in vivo post-coitally as well as ex vivo, collected from the female reproductive tract. Ex vivo ejaculated sAC null sperm behaved similarly to epididymal sAC null sperm, except with respect to the physiologically induced acrosome reaction. These studies suggest there is a sAC-independent regulation of acrosome responsiveness induced upon ejaculation or exposure to factors in the female reproductive tract. We also studied the behavior of sAC null sperm in vivo post-coitally by taking advantage of transgenes with fluorescently labelled sperm. Transgenes expressing GFP in the acrosome and DsRed2 in the mitochondria located in the midpiece of sperm (DsRed2/Acr3-EGFP) allow visualization of sperm migration through the female reproductive tract after copulation. As previously reported, sperm from wild type (WT) double transgenic mice migrated from the uterus through the uterotubular junction (UTJ) into the oviduct within an hour post-copulation. In contrast, sperm from sAC null double transgenic mice were only found in the uterus. There were no sAC null sperm in the oviduct, even 8 hours after copulation. These results demonstrate that sAC KO males are infertile because their sperm do not migrate to the fertilization site.